SIMULATION SOFTWARE FOR MODELING THE MOVEMENT OF MATERIAL FLOWS: SIMULATION SOFTWARE FOR MODELING THE MOVEMENT OF MATERIAL FLOWS - Antonov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The Computer modeling is one of the best tools for the development of a real automated warehouse system. It aims to explore and define the behavior of the system and make the evaluation of its performance. In this paper is analyzed and simulated a software for the design of logistic systems.